1975
DOI: 10.1042/bj1470283
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of S-substituted cysteines by a rat liver and kidney microsomal N-acetyltransferase

Abstract: 1. An acetyl-CoA--S-substituted cysteine N-acetyltransferase in rat liver and kidney preparations was investigated, by using an assay involving incubations with S-benzyl-L-cysteine and [l-14C]acetyl-CoA and extraction of the radioactive product with ethyl acetate. 2. The enzyme was associated with the microsomal fraction and could not be solubilized. Metal ions, EDTA and detergents did not significantly affect the enzyme activity. p-Chloromercuribenzoate and N-ethylmaleimide inhibited the enzyme. 3. Other S-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 33 publications
(21 reference statements)
2
16
0
Order By: Relevance
“…when the cysteine conjugate of benzyl isothiocyanate was incubated with liver or kidney homogenates in the presence of acetyl-CoA. Both the liver and kidneys of rats have been shown to catalyse the N-acetylation of cysteine conjugates (Green & Elce, 1975). Limited acetylation also occurred in the absence of the homogenates or in the absence of acetyl-CoA, indicating respectively non-enzymic acetylation and the presence of sufficient acetyl-CoA in the homogenates to produce detectable amounts of mercapturic acid.…”
Section: Resultsmentioning
confidence: 99%
“…when the cysteine conjugate of benzyl isothiocyanate was incubated with liver or kidney homogenates in the presence of acetyl-CoA. Both the liver and kidneys of rats have been shown to catalyse the N-acetylation of cysteine conjugates (Green & Elce, 1975). Limited acetylation also occurred in the absence of the homogenates or in the absence of acetyl-CoA, indicating respectively non-enzymic acetylation and the presence of sufficient acetyl-CoA in the homogenates to produce detectable amounts of mercapturic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Activity assays with radioactive substrates have shown that the specific activity of CCNAT for Cys conjugates in rat kidneys is nearly two-fold greater than that found in liver (Green and Elce, 1975). Mercapturates formed in the liver are secreted into the bile, where they usually undergo enterohepatic circulation and eventually reach the kidneys (Silbernagl and Heuner, 1990).…”
Section: Cysteine S-conjugate N-acetyltransferasementioning
confidence: 99%
“…Studies on microsomal preparations have shown that the active site of CCNAT is localized to the cytoplasmic side of the endoplasmic reticulum (ER) (Elce, 1970;Green and Elce, 1975;Okajima et al, 1984). The CCNAT co-substrate acetyl-CoA is localized in the cytosol at high concentrations to facilitate rapid and efficient N-acetylation of Cys conjugates (Garland et al, 1965).…”
Section: Cysteine S-conjugate N-acetyltransferasementioning
confidence: 99%
“…It is important to note that the shuttling of the cysteine conjugates back to the liver is analogous to that of amino acids and dipeptides released after the renal degradation of GSH, 1) where the amino acids and dipeptides, such as glutamic acid and cysteinylglycine formed from GSH by renal g-GT and dipeptidases, can be rapidly transported back to the liver for synthesis of new GSH. 15,16) Since the kidney has enough N-acetyltransferase activity (243 nmol/min/kidney towards BCys) to N-acetylation of cysteine conjugates (BCys AUC after BSG administration; 160 nmol/min/kidney) and a specific activity nearly the same as ( Table 1) or twice that of the liver, 9,17) the shuttling of S-carbamidomethyl cysteine back to the liver for acetylation is puzzling. Given these findings, such a small cysteine conjugate as S-carbamidomethyl cysteine would probably be incorporated into the interorgan metabolism of GSH.…”
Section: Chemicalsmentioning
confidence: 99%
“…N-Acetyltransferase Activity Microsomal N-acetyltransferase activity towards BCys was assayed by the modified procedure of Green et al 9) in which cold acetyl-CoA was used instead of [ 14 C] acetyl-CoA. The addition of the same volume of dimethyl sulfoxide (DMSO) as the incubation mixture terminated the enzyme reaction, and the mixture was centrifuged at 15000ϫg for 5 min.…”
Section: Chemicalsmentioning
confidence: 99%